1985
DOI: 10.1016/0014-5793(85)80407-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of platelet cytosolic free calcium by cyclic nucleotides and protein kinase C

Abstract: PAF elicits a rapid, concentration-dependent elevation of platelet cytosolic free calcium ([Car]), measured by quin2. Elevation of [Car] is transient, and the rate of reversal increases with agonist concentration. Adenylate cyclase stimulants (PGI,, PGDJ and 8-bromo CAMP; a guanylate cyclase stimulant (sodium nitroprusside) and 8-bromo cGMP; and a protein kinase C stimulant (phorbol myristate acetate) block the elevation of [Car] induced by PAF, and accelerate its reversal. These results suggest that CAMP, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(12 citation statements)
references
References 25 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…Halenda et al [13,14] have shown that the active phorbol esters potentiate AA release induced by the Ca2+ ionophore A23187 in platelets, and this potentiation has been interpreted in terms of activating phospholipase A2 by the protein kinase C system. However, phorbol 12-myristate 13-acetate (PMA) alone, which does not mobilize Ca2+ [15,16], is able to release AA [17]. Thus factors other than phospholipase A2 activation, such as inhibition of AA re-incorporation [18] or stimulation of transacylase reactions, might be involved in the protein kinase C-dependent AA release.…”
Section: Introductionmentioning
confidence: 99%
“…Halenda et al [13,14] have shown that the active phorbol esters potentiate AA release induced by the Ca2+ ionophore A23187 in platelets, and this potentiation has been interpreted in terms of activating phospholipase A2 by the protein kinase C system. However, phorbol 12-myristate 13-acetate (PMA) alone, which does not mobilize Ca2+ [15,16], is able to release AA [17]. Thus factors other than phospholipase A2 activation, such as inhibition of AA re-incorporation [18] or stimulation of transacylase reactions, might be involved in the protein kinase C-dependent AA release.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibition is mediated through lowering the Ca, (11)(12)(13)(14)(15)(16)27) and via Ca-independent mechanisms (28). Blunting 'or ablating of agonistevoked Cai response by cyclic nucleotides involve key elements ofCa, homeostasis, including inhibition of(a) agonist-receptor interaction (29); (b) PLC (11,12,30,31); (c) Ca mobilization from intracellular organelles (26,27,30,32); and (d) Ca uptake from the extracellular compartment (27, 30, 32).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic nucleotides are cellular messengers that inhibit platelet aggregation and diametrically antagonize Cai in these cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). We have thus focused this investigation on the role of cyclic nucleotides in modulating parameters of the Na/H antiport.…”
Section: Introductionmentioning
confidence: 99%
“…Using TPA and human platelets we have recently shown that, besides mediating cellular activation, protein kinase C may also regulate agonist-induced Ca2+ flux (MacIntyre et al, 1985). In the present study we examined the effects of TPA on changes in [Ca2+]i in human neutrophils elicited by the chemotactic tripeptide formylmethionylleucylphenylalanine (FMLP), leukotriene B4 (LTB4) and 1-0-hexadecyl-2-acetyl SN glycero-3-phosphorylcholine (platelet-activating factor, PAF).…”
Section: -Ht2 Receptor Bindingmentioning
confidence: 99%
“…Thus, SCH 23390 blocks stereotypy induced both by apomorphine and by the selective D-2 agonist RU 24213 (Molloy & Waddington, 1984, 1985O'Boyle et al, 1984). SK&F 83566 is a potent D-1 antagonist, this action residing in its R-but not S-enantiomer; residual D-2 antagonist activity is weak and shows negligible enantioselectivity (O'Boyle & Waddington, 1984 motor responses which were promptly abolished by tetrodotoxin (TTX), (3x10-7M).…”
mentioning
confidence: 99%